0386 Occupational noise exposure and ambulatory blood pressure: the exposure response relation with acute and lagged exposure. (21st August 2017) - Stokholm, Zara Ann; Christensen, Kent Lodberg; Frederiksen, Thomas W; Vestergaard, Jesper M; Hansen, Åse Marie; Bonde, Jens Peter; Kristiansen, Jesper; Lund, Søren Peter; Kolstad, Henrik A
Abstract : Background: Long-term environmental noise exposure has repeatedly been related to increased risk of cardiovascular disease at exposure levels as low as 35 dB(A). Occupational exposure levels are orders of magnitude higher than the environmental levels. We examined if blood pressure was increased during and subsequent to occupational noise exposure. Methods: We studied 483 industrial, finance, and service workers selected as a random sample from 10 industrial trades and financial services between 2009 and 2010. For 24 hours, we recorded noise exposure levels every 5 s by personal dosimeters and measured ambulatory blood pressure and heart rate every 20–30 min. In mixed linear regression models, we assessed the acute and lagged effects of ambient noise exposure (LAEq)) on blood pressure and heart rate for work, leisure and night hours. For 319 workers, we estimated these effects for noise exposure at the ear accounting for hearing protection use. Results: Full-shift occupational noise exposure levels ranged between 59–97 dB(A). Results of the regression models adjusted for sex, age, income, BMI, alcohol, tobacco, salt intake, and family history of hypertension suggest no relation between acute or lagged occupational noise exposure level and blood pressure levels for the industrial workers. Conclusion: Occupational noise exposure showed no acute or lagged effects on blood pressure in industrial workers.